Flipped Classroom Model in High School Mathematics - Tekin, Oğuzhan; Sarıkaya, Esma Emmioğlu (Bartın Üniversitesi, 2020)
The aim of this study was to examine the effect of the flipped classroom model on 10th grade students' mathematics achievement and mathematical attitudes. The research has as a pre test post test quasi-experimental design with a control group. The participants consisted of 67 tenth grade students in two groups as control (n=33) and experiment (n=34). A non-interventional, regular mathematics instruction (technology integrated face to face classroom model) currenlty being implemented by state schools was applied in the control group. Flipped classoom model was used in the experimental group. The data were collected by using the “Mathematics Achievement Test” and the “Attitudes towards Mathematics Instrument”. In the analysis of the data, a repeated samples t-test and independent samples t-test were used. The critical value was taken as .05 for all statistical tests. The findings of the study revealed that the experimental group students in flipped classroom model had statistically significantly higher scores on both mathematics achievement and mathematical attitudes than the control group students. Based on the findings of the current study, it was suggested that, flipped classroom model can be used in high school mathematics courses.
Keywords: Other Fields of Education; Alan Eğitimleri